Effects of Soil and Water Conservation at Different Landscape Positions on Soil Properties and Farmers’ Perception in Hobicheka Sub-Watershed, Southern Ethiopia - Tamrat Sinore; Dinsa Doboch (Applied and Environmental Soil Science)
This study aimed to evaluate the effects of soil and water conservation (soil bund with desho grass and soil bund only) at different landscape positions on selected soil properties and farmers’ perception in the Hobicheka sub-watershed (with an area of 400 ha) of Kechabira District. Composite soil samples were taken from soil bunds with desho grass and soil bunds only at three landscape positions with three replications, whereas 117 respondents were identified using simple random sampling. The result revealed that the clay, soil moisture content, soil pH, OC, TN, Av.P, and CEC were higher in soil bund with desho grass as compared to adjacent soil bund only, whereas, bulk density, silt, and sand contents were higher in adjacent soil bund only compared to soil bund with desho grass. About 83.5% of the respondents were users of soil and water conservation measures and among them, 40.19% perceived that soil bund with desho grass has an effect on soil properties, while 25.35% perceived that soil bund only had better soil and water conservation practices. Respondents’ years of experience, education level, and access to soil and water conservation extension services significantly (p≤0.1) affected their perception of the use of soil bunds with desho grass. Therefore, soil bund with desho grass at appropriate landscape positions by considering farmer perception improves the soil’s physicochemical properties.